Comparing Concept Drift Detection with Process Mining Tools - Omori, Nicolas Jashchenko; Tavares, Gabriel Marques; Ceravolo, Paolo; Barbon Jr., Sylvio (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2019)
Organisations have seen a rise in the volume of data corresponding to business processes being recorded. Handling process data is a meaningful way to extract relevant information from business processes with impact on the company’s values. Nonetheless, business processes are subject to changes during their executions, adding complexity to their analysis. This paper aims at evaluating currently available Process Mining tools that handle concept drifts, i.e. changes over time of the statistical properties of the events occurring in a process. We provide an in-depth analysis of these tools briefly comparing their differences, advantages, and disadvantages.